The Process of Democratization in Yogyakarta, Indonesia, 1951â1956: A Historical Perspective - Yuniyanto, Tri (ASPENSI in Bandung, Indonesia, 2010)
ABSTRACT: Democracy is government by people, or in any case, people are involved in decision making concerning the problems management of government. Government of democracy can run passing two ways that is democracy directly and indirectly. In modern state, government of democracy in general executed indirectly, that is through the existence representative institutes represent people. Since Indonesia gained its independence, there were basic changes to build the political order democratically. Hence, it is important to note here for knowing the process of democratization in Yogyakarta. Like other self governing area, in Yogyakarta also claimed to be able to execute order of government of democracy. Social and political stucture in Yogyakarta gave a great change to excecutive institution to be more dominant in determining policy of regional government. DPRD (Dewan Perwakilan Rakyat Daerah), for example, as tool to run peopleâs sovereignity in determining regional governmnet policy, was real not only as ârubber stampâ of policy which was determined by DPD (Dewan Pemerintahan Daerah), but also were able to give control and correction against deviation which happened. KEY WORDS: Process of democratization, General Election, regional government, regional representative council, and social and political control.About the Author: Tri Yuniyanto, M.Hum is a Lecturer at the Department of History Education, Faculty of Education and Teacher Training UNS (State University of Solo), Jalan Ir. Sutami No.36-A, Kentingan, Surakarta, Central Java, Indonesia. He can be reached at: triyuniyanto@gmail.comHow to cite this article? Yuniyanto, Tri. (2010). âThe Process of Democratization in Yogyakarta, Indonesia, 1951â1956: A Historical Perspectiveâ in TAWARIKH: International Journal for Historical Studies, Vol.2(1) October, pp.61-74. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (August 3, 2010); Revised (September 6, 2010); and Published (October 28, 2010).